SOME PROPERTIES OF COMPLEX QUATERNION AND COMPLEX SPLIT QUATERNION MATRICES - Alagoz, Y.; Ozyurt, G. (UNIV MISKOLC INST MATH, 2019)
The aim of this study is to investigate some properties of complex quaternion and complex split quaternion matrices. To verify this, we use 2x2 complex matrix representation of these quaternions. Moreover, we present a method to find the determinant of complex quaternion and complex split quaternion matrices. Finally, we research some special matrices for quaternions above.
Keywords: complex quaternion matrix; complex split quaternion matrix; Mathematics